An Important Tool in Lymphedema Management: Validation of the Turkish Version of the Gynecologic Cancer Lymphedema Questionnaire - Hanife Abakay; Ummuhan Abdulrezzak; Turkan Akbayrak (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: This study aimed to research the reliability and validity of the Turkish version of the gynecologic cancer lymphedema questionnaire for individuals with gynecologic cancer.